Place and role of multifield hospital in teaching program on surgery for students - A. V. Kapshytar (Zaporožskij Medicinskij Žurnal)
Present time is characterized by increase of dynamics of world and social development, introduction of ECTS (European Credit Transfer System) [Andrushchenko V. P. at al. 2007; Pertseva T. O. at al. 2008]. Features of new information technologies and forms of educational process dictate need of active introduction of the principles of evidential medicine [Pidayev A. Century at al. 2004; Pishak at al. 2005; Bereznitsky Y. S. at al. 2006]. Thus the main postulate of the Bologna declaration is providing adequate material level of educational base where the training program is implemented in the hospital [Desyaterik V.I. 2008].